Nutrition Care Process Model Approach to Surgical Prehabilitation in Oncology - Gillis, Chelsia; Hasil, Leslee; Kasvis, Popi; Bibby, Neil; Davies, Sarah J.; Prado, Carla M.; West, Malcolm A.; Shaw, Clare (Frontiers in Nutrition, 2021)
The nutrition care process is a standardized and systematic method used by nutrition professionals to assess, diagnose, treat, and monitor patients. Using the nutrition care process model, we demonstrate how nutrition prehabilitation can be applied to the pre-surgical oncology patient.